(untitled) (Journal of the College of Basic Education, 2023)
The research aims to identify the deep understanding and its relationship to deductive thinking among the students of the third intermediate grade in mathematics. The research sample consisted of (400) female students in some schools affiliated to the General Directorate of Education of Baghdad / Al-Rusafa II, where the researcher adopted the test (Al-Mashhadani, 2021) for deep understanding and relied in preparing the items for the deductive reasoning test on previous literature and studies, using the (t) test and coefficient Pearson’s correlation to compare the results. The results revealed: 1- There is a statistically significant difference at the level of significance (0.05) between the hypothetical mean and the arithmetic mean of the grades of the third intermediate grade students in the deep understanding test and the deductive thinking test, in favor of the arithmetic mean. 2- There is a positive statistically significant correlation between the scores of the third intermediate grade students in the deep understanding test and their scores in the deductive thinking test. In the light of the results of the research, the researcher concluded that the level of the third intermediate grade students was good in the deep understanding test and the deductive thinking test, and there was a positive correlation between deep understanding and inferential thinking, and she recommended a number of recommendations and proposals.